STRATEGI PEMBELAJARAN DENGAN MENGGUNAKAN KONTEKSTUAL - Ulfaidah Ulfaidah; Agus Purna Irawan; Nilam Solikhatin Firda; Muhammad Irman Fatma Wiguna; Suparmanto Suparmanto (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2022)
Many factors influence the success of the learning process, including language learning. Student problems in learning language Arabic is students still need a long time to learn andimplement Arabic. Contextual learning model (contextual teaching and learning) is present in this era with the aim of helping students understand the meaning of teaching materials and relate them to the context of everyday life. The purpose of this study is to discuss in depth the theory of strategy contextual learning in learning Arabic. Deep data source. This research is a variety of literature books, journals, scientific papers, and also other documents both in physical and digital form are reviewed regarding contextual strategy. Data analysis techniques used in research this is a data analysis technique according to Matthew B. Miles and A. Michael Huberman which consists of 4 stages, namely data collection, data reduction, data display, and conclusion